Sufism-Based Management for Improving Working Performance in the 4.0 Industrial Era: A Phenomenological Perspective - Suwito, Suwito; Nugroho, Ischak Suryo; Mualim, Maulana; Sarastuti, Eka Septiani (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2023)
Sufism is often understood as an approach to cleansing one's soul (tazkiyat al-nafs). Its infusion to human resource management is severely underutilised. This article aims to describe the managerial experience and services of a Sufism-based institution, namely the Faculty of Tarbiyya and Teacher Training UIN Prof. K.H. Saifuddin Zuhri, Purwokerto. The faculty has implemented Sufism-based management to improve its employee performance in the industrial revolution 4.0. This paper is qualitative research with a phenomenological approach. Data are collected through participatory observation, in-depth interviews, and documentation. Twelve key informants comprising officials, lecturers, administrative staff, and students, were invited. The data were then analysed by employing Smith's model. The finding showed that spiritually clean and healthy officials could stimulate wiser organisational behaviour, stimulate bright ideas (innovations), and shape a stronger desire to follow up on problems. This Sufism-based management supports the improvement of the service quality of the institution internally, externally, and eternally.Contribution: This study contributes to the literature on Sufism-based management in the sense of providing practical implementation of takhallī, taḥallī, and tajallī in management